Analysis of the Influence of Digital Marketing on Consumer Loyalty in the Industry 4.0 Era - Musthofa Kamal; Tiyus Martha Kurniadi; Lintang Sandy Tria Sakti; Chamariyah, Chamariyah (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of digital marketing on consumer loyalty in the Industry 4.0 era. In this context, digital marketing is defined as the use of digital technologies, such as social media, email marketing, and other online platforms, to promote products and interact with consumers. Consumer loyalty is a crucial factor for a company's long-term survival and success. The method used in this study is a literature review by collecting various relevant sources from previous research related to digital marketing and consumer loyalty. The results show that digital marketing has a positive influence on consumer loyalty, both through increasing customer satisfaction, building trust, and increasing consumer interaction and engagement. In addition, factors such as product quality, innovation, and satisfying consumer experiences also play a role in strengthening loyalty. This study contributes to companies' understanding of the importance of digital marketing in maintaining consumer loyalty in this increasingly developing era. It is hoped that companies can optimize the use of digital marketing to build better relationships and increase customer loyalty levels.